Electronic Medical Records and Physician Productivity: Evidence from Panel Data Analysis - Bhargava, Hemant K.; Mishra, Abhay Nath (Management Science, 2014)
This paper studies the impact of an electronic medical record (EMR) system on the productivity of physicians. Physicians influence a vast majority of treatment decisions and are central to the care delivery process; thus, it is important to understand how EMRs may impact the nature of their work. Our research builds on prior literature on physician productivity, IT productivity, and task–technology fit theory. We use a unique panel data set comprising 87 physicians specializing in internal medicine, pediatrics, and family practice, located in 12 primary care clinics of an academic healthcare system in the western United States. We employ the Arellano–Bond system generalized method of moments estimation technique on our data set, which contains 3,186 physician-month productivity observations collected over 39 months. We find that productivity drops sharply immediately after technology implementation and recovers partly over the next few months. The ultimate, longer-term impact depends on physician specialty. The net impact of the EMR system is more benign on internal medicine physicians than on pediatricians and family practitioners. We postulate that the fit provided by an EMR system to the task requirements of physicians of various specialties may be key to disentangling the productivity dynamics. Our research finds that on one hand, present-day EMR systems do not produce the kind of productivity gain that could lead to substantial savings in healthcare; at the same time, EMRs do not cause a major productivity loss on a sustained basis, as many physicians fear. This paper was accepted by Lorin Hitt, information systems.